Antioxidant mechanisms to counteract TiO2-nanoparticles toxicity in wheat leaves and roots are organ dependent - Silva, Sónia (2019)
Nanoparticles (NP) bioactivity is under deep scrutiny. In this work, the antioxidant response to TiO2-NP in wheat (Triticum aestivum) was determined. For that, enzymatic and the non-enzymatic antioxidants were evaluated in plants exposed to the P25 anatase:rutile material composed of TiO2-NP and under environmentally realistic doses (0; 5; 50; 150 mg/L for 20 days). Shoot but not root growth was reduced. In leaves, thiol metabolism and ascorbate accumulation were the preferred route whereas in roots the pre-existing antioxidant capacity was preferentially utilized. Both leaves and roots showed increased glutathione reductase and dehydroascorbate reductase activities and decreased ascorbate peroxidase activity. Roots, nevertheless, presented higher enzymatic basal levels than leaves. On the other hand, when examining non-enzymatic antioxidants, the ratio of reduced-to-oxidized glutathione (GSH/GSSG) increased in leaves and decreased in roots. Exposed leaves also presented higher total ascorbate accumulation compared to roots. TiO2-NP exposure down regulated, with more prominence in roots, antioxidant enzyme genes encoding catalase, ascorbate peroxidase, monodehydroascorbate reductase and dehydroascorbate reductase. In leaves, superoxide dismutase gene expression was increased. All data pinpoint to TiO2-NP toxicity above 5 mg/L, with aerial parts being more susceptible, which draws concerns on the safety doses for the use of these NPs in agricultural practices.